The Cancer Mycobiome: A Highlight to Lung Cancer - Yuwono, Edho; Zaini, Jamal; Rozaliyani, Anna (Faculty of Medicine Universitas Airlangga, 2024)
Microbiota is a collection of microorganisms such as bacteria, fungi, viruses, and archaea, with bacteria being the most numerous in the human body. Meanwhile, the mycobiome consists of commensal fungi, which are a small part of the microbiota. Examples found in the human body, from the skin to the internal organs, play a role in the immune response, homeostasis, metabolism, and disease. The composition of mycobiome varies over time, and the human intestine is the most studied organ due to the diversity of microbiota. Furthermore, lung cancer is the leading cause of death in oncology patients worldwide. Various studies suggest that mycobiomes play a role in cancer associated with dysbiosis. Chronic inflammation, biofilm formation, and carcinogen products are parts of cancer pathogenesis. Metagenome analysis has provided information about the diversity of microbiota, specifically mycobiome in the human body. The common method for gene sequencing in the metagenome is next-generation sequencing (NGS). Analysis through metagenomes in chronic diseases such as cancer shows that mycobiomes play a role in the process of cancer formation. However, the causal relationship between mycobiomes and cancer remains unknown.